Exploring the functional quality attributes of smart home for older adults based on qualitative research and Kano model - Yang, Qin; Li, Peishan; Liu, Xing; Wei, Chunnan (Frontiers in Public Health, 2025)
BackgroundThis study investigates the functional attributes of smart home for older adults across different age groups, aiming to identify features that fulfill users’ needs and give convenience, thereby offering scientific guidance for future smart home designs for older adults.MethodsEmploying a multi-stage approach, this study commences with semi-structured interviews with older participants in China, analyzing transcripts using NVivo to guide questionnaire design. Subsequently, a questionnaire survey is administered to older adults in China, with the data processed using the Kano model incorporating the Better-Worse index with sensitivity coefficients.ResultsThe findings distinctly demonstrate divergent preferences among different age groups. Specifically, for older adults aged 60–69, health, life and entertainment functions emerge as top priorities, identifying two indicators classified as Must-be quality, five as One-dimensional quality, and one as Attractive quality. In contrast, among those older adults aged 70 and above, emphasis lies predominantly on health, life and emotion functions, identifying one indicator categorized as Must-be quality, six as One-dimensional quality and two as Attractive quality.ConclusionThis study highlights the existence of significant variations in the needs of different older adult age groups. Through the classification of functional attributes of smart home for older adults, development strategies can be precisely formulated to better meet the needs of different age groups.